Multilingual reading interventionists for junior high school: a response to the Philippines’ functional literacy gap - Manuel, Jeremiah Paul Giron; Gatcho, Al Ryanne Gabonada; Areta, Gerry Cabrera (Frontiers in Education, 2025)
Functional illiteracy remains a persistent and complex issue in the Philippines, as underscored by data from the 2024 Functional Literacy, Education, and Mass Media Survey (FLEMMS). Overlapping challenges such as socioeconomic inequality, linguistic diversity, limited instructional support, and restricted language access continue to hinder literacy efforts despite numerous interventions. This policy brief evaluates current responses and proposes the institutionalization of Multilingual Reading Interventionists (MRIs) in junior high schools as a strategic way forward. Trained in regional languages and grounded in local contexts, MRIs are envisioned as school-based professionals who provide equitable, culturally responsive, and differentiated reading support. To realize this proposal, key policy directions include integrating MRI training into teacher education institutions, aligning continuing professional development systems, and creating formal teaching positions under the Department of Education.